2013
DOI: 10.1179/1973947812y.0000000061
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, pharmacodynamics and efficacy of novel FabI inhibitor AFN-1252 against MSSA and MRSA in the murine thigh infection model

Abstract: AFN-1252, a new antimicrobial agent, specifically and potently inhibits fatty acid synthesis in Staphylococcus aureus. We characterized in vivo pharmacokinetic and pharmacodynamic profiles of AFN-1252 administered orally to neutropenic mice inoculated in thighs (∼106 CFU) with methicillin-susceptible S. aureus (MSSA) ATCC 29213. Efficacy was also assessed in mice inoculated with MSSA, hospital-acquired Methicillin-resistant Staphylococcus aureus (HA-MRSA) or community-acquired (CA)-MRSA, and administered AFN-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 9 publications
1
45
0
1
Order By: Relevance
“…Although previous work suggested that fatty acids and phospholipids of chlamydial membranes are obtained from the host (45), our study shows that FASII is nonetheless essential for chlamydial replication. AFN-1252 is effective in cell culture against C. trachomatis and has pharmacological properties that make it an effective agent against S. aureus infections (36,46). However, its potency may have to be improved in order for it to be effectively deployed to treat C. trachomatis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous work suggested that fatty acids and phospholipids of chlamydial membranes are obtained from the host (45), our study shows that FASII is nonetheless essential for chlamydial replication. AFN-1252 is effective in cell culture against C. trachomatis and has pharmacological properties that make it an effective agent against S. aureus infections (36,46). However, its potency may have to be improved in order for it to be effectively deployed to treat C. trachomatis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, AFN-1252 is a sharp tool to study the effects of FASII inhibition on C. trachomatis replication in light of its selectivity, its binding affinity, and the absence of off-target effects on human cells (11,36).…”
Section: ⅐Afn-1252 Complex These Data Indicated That Afn-1252 Inhibitedmentioning
confidence: 99%
“…236 Affinium licensed the program in 2002 and conducted further structure optimization leading to AFN-1252 (39). 232,[238][239][240][241][242][243][244][245] In February 2014, Debiopharm Group (Lausanne, Switzerland) acquired Affinium's antibiotic assets, including both 39 and a prodrug of AFN-1252, Debio-1450 (AFN-1720). 246 The prodrug, Debio-1450, was assessed in two phase-I studies (NCT02162199 and NCT02214433), with a third (NCT02595203) scheduled for completion in December 2015.…”
Section: Compounds Undergoing Clinical Evaluationmentioning
confidence: 99%
“…Thus, acc knockouts must scavenge lipoate as well as fatty acids from the host, and our experiments illustrate that the quality and/or availability of these nutrients in mice attenuates the virulence of the bacteria. Our data provide a mechanistic rationale for the observed efficacy of the ACC inhibitors against S. aureus infections (21) and for the lack of acc mutations arising in animals treated with AFN-1252 (6,22) or other FASII inhibitors (23)(24)(25)(26).…”
mentioning
confidence: 99%